Aquaculture in Maritime Spatial Planning Frameworks and Its Contribution to Global Food Security - Øivind Strand; Hui Liu; Joao G. Ferreira; Ramon Filgueira; Ellen Sofie Grefsrud; Pia Kupka Hansen; Qianwen Sun; Jenny Weitzman (Reviews in Aquaculture, 2026)
Increase in aquaculture toward realizing the potential of the ocean as a key food provider requires comprehensive and proactive management approaches to mitigate impacts on coastal areas and to secure space for sustainable aquaculture development in both inshore and offshore areas. Maritime Spatial Planning (MSP) and Marine Functional Zoning (MFZ) are policy instruments employed in the management and regulation of multiple human activities to balance social, economic, and environmental objectives. This work reviews the processes and stages of aquaculture integration into these marine spatial planning frameworks (MSP and MFZ) in major producers, China, the EU, Norway, and Canada. Implementation of aquaculture in the spatial planning frameworks varies widely, partly because the nations reviewed are at different stages of aquaculture development, and partly due to the heterogeneity of institutions, traditions, social acceptance, marine space, and governance. The common challenge of aquaculture impacts and interactions with the environment contribute to the complexity of regulating space for mariculture development. The apparent weak and in some cases receding position of aquaculture in the maritime spatial planning frameworks reviewed here warrants considerable concern with respect to expectations of marine aquaculture as a route for ensuring future seafood provision. There is a need to strengthen the position of aquaculture in marine spatial planning frameworks, particularly when considering its expansion in areas with potential for development. It is recommended that the global scientific, management, and regulatory communities work together with local actors to develop and provide accessible tools that will address sustainability challenges ahead.

Environmental indicators in salmon aquaculture research: A systematic review - Megan E. Rector; Jenny Weitzman; Ramón Filgueira; Jon Grant (Reviews in Aquaculture, 2022)
The ecosystem approach to aquaculture (EAA) is a strategy for the sustainable development of the aquaculture sector, but the question of how it can be practically implemented remains unclear. Indicators that can be applied at relevant scales of impact and that reflect the environmental status and change offer a means of operationalizing EAA. Therefore, a systematic literature review was carried out to identify environmental indicators referenced in salmon aquaculture literature and review their potential to support EAA. Using the PRISMA method for selecting journal papers, 101 articles that included 531 indicators were reviewed. Indicators were characterized based on the effect of aquaculture they measure, their similarity to other indicators extracted, and the scale at which they were applied. Indicators and their characteristics are presented in a searchable online database. A scoring method for evaluating indicators based on criteria drawn from environmental indicator literature and the potential scalability of indicators to meet the needs of EAA was developed and applied to the most frequently referenced indicators. Overall, near‐field indicators of benthic impacts dominated salmon aquaculture literature. Of the most frequently referenced indicators, those that scored highest based on criteria drawn from environmental indicator literature also scored highest on scalability and therefore their potential contribution to EAA. Overall, results suggest that additional research and application of far‐field environmental indicators in salmon aquaculture will be required to identify a suite of indicators that can be applied as part of EAA practice.

The evolution and application of carrying capacity in aquaculture: towards a research agenda - Jenny Weitzman; Ramón Filgueira (Reviews in Aquaculture, 2020)
Carrying capacity has become a fundamental concept within the context of environmental management. Carrying capacity for aquaculture has been studied since the 1960s and has attracted a dedicated literature focused on measuring the environmental and production limits of aquaculture developments. Nevertheless, management and policy face emerging challenges across environmental and social aspects and the growing need to manage multiple objectives in increasingly crowded aquatic ecosystems. Therefore, promoting more sustainable aquaculture development should consider how the tools, methods and research used to support management and decision‐making should advance to meet such challenges. Here, the conceptual and practical applications of carrying capacity are reviewed and future prospects discussed. Carrying capacity for aquaculture has developed a range of models, indicators and approaches to study the relationships between aquaculture and ecosystem components. Carrying capacity supports diverse management objectives to support physical, production, ecological and social goals, although greater emphasis has focused on ecological and production capacities. This review introduces research needs and strategies to advance methods and tools and improve carrying capacity utilization for more holistic, ecosystem‐based aquaculture decision‐making. This paper presents a five‐pillar research agenda for carrying capacity that (i) recognizes system complexity and is (ii) policy‐relevant, (iii) adaptive, (iv) interdisciplinary and (v) meaningful. By promoting knowledge uptake and addressing literature gaps, the proposed agenda could help operationalize a holistic approach to managing for aquaculture sustainability.